1979
DOI: 10.1111/j.1365-2125.1979.tb04765.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of labetalol on continuous ambulatory blood pressure.

Abstract: 1 The hypotensive action of labetalol was evaluated during 24 h by continuous intra‐arterial ambulatory monitoring in 14 patients. The dose used ranged from 300–1800 mg daily. 2 The drug caused a significant reduction of systolic BP in 19 and diastolic BP in 20 of the 24 h of monitoring. Heart rate was also reduced but less markedly than BP. 3 The rapid early morning increase in BP was also effectively controlled. 4 The mild pre‐waking increase in BP was not significantly reduced. 5 Labetalol treatment reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Any benefit derived from a lowered blood pressure at this time is unknown but it is interesting that agents which act by causing a reduction in the peripheral resistance, when studied using intra-arterial ambulatory monitoring, have all caused a reduction of the blood pressure at this time (Raftery et al, 1981;Gould et al, in press). The only agent which has altered the shape of the circadian curves was labetalol (Balasubramanian et al, 1979). These findings suggest indoramin is behaving more like a vasodilator than an ac-blocker.…”
Section: Discussionmentioning
confidence: 91%
“…Any benefit derived from a lowered blood pressure at this time is unknown but it is interesting that agents which act by causing a reduction in the peripheral resistance, when studied using intra-arterial ambulatory monitoring, have all caused a reduction of the blood pressure at this time (Raftery et al, 1981;Gould et al, in press). The only agent which has altered the shape of the circadian curves was labetalol (Balasubramanian et al, 1979). These findings suggest indoramin is behaving more like a vasodilator than an ac-blocker.…”
Section: Discussionmentioning
confidence: 91%
“…No fall in nocturnal blood pressure and a rise in the early morning may be characteristic of SAS. Raffery et al and DeQuattro et al reported that the rise in blood pressure in the early morning is due to the initiation of alpha-sympathetic nervous activity (18,19). No fall in the nocturnal blood pressure and the rise in the early morning in SAS patients may indicate activation of the sympathetic nervous system at night and in the early morning.…”
Section: Resultsmentioning
confidence: 98%
“…3 Although continuous intraarterial ambulatory blood pressure monitoring was then feasible in patients, the method was cumbersome and received little acceptance by patients. 4 A practicable advance was the development of indirect 24-hour ambulatory blood pressure monitoring (ABPM) that was compared with direct measurements. 5 This method has developed technically so that acceptance by patients is no longer a problem.…”
mentioning
confidence: 99%